COVID‐19 in children. II: Pathogenesis, disease spectrum and management. (25th October 2021) - Howard‐Jones, Annaleise R; Burgner, David P; Crawford, Nigel W; Goeman, Emma; Gray, Paul E; Hsu, Peter; Kuek, Stephanie; McMullan, Brendan J; Tosif, Shidan; Wurzel, Danielle; Bowen, Asha C; Danchin, Margie; et al.
Abstract : The global disruption of the COVID‐19 pandemic has impacted the life of every child either directly or indirectly. This review explores the pathophysiology, immune response, clinical presentation and treatment of COVID‐19 in children, summarising the most up‐to‐date data including recent developments regarding variants of concern. The acute infection with SARS‐CoV‐2 is generally mild in children, whilst the post‐infectious manifestations, including paediatric inflammatory multisystem syndrome temporally associated with SARS‐CoV‐2 (PIMS‐TS) and 'long COVID' in children, are more complex. Given that most research on COVID‐19 has focused on adult cohorts and that clinical manifestations, treatment availability and impacts differ markedly in children, research that specifically examines COVID‐19 in children needs to be prioritised.